DEVELOPMENT OF CHEMISTRY INSTRUCTION MATERIAL USING PROBLEM BASED LEARNING MODEL FOR INCREASING THE STUDENT OF SENIOR HIGH SCHOOL LEARNING ACHIEVEMENT - Syifaiyah, Robiatusy; Tukiran, Tukiran; Erman, Erman (JPPS (Jurnal Penelitian Pendidikan Sains), 2018)
This research aims to develop chemistry learning materials PBM models oriented in curriculum 2013 to improve learning outcomes of high school students on the material factors that affect the rate of reaction. This research is the development by using Kemp models,et al. Limited trial design uses one group pretest posttest design with descriptive analysis techniques of quantitative and qualitative descriptive. This study uses the subject of the trial class XI SMA-Based Leading Pesantren Amanatul Ummah 2015-2016 school year on the subject of factors that affect the rate of reaction. The results showed: (1) The quality of the device can be seen from the validation RPP, validation BAS, validation worksheets, and validation of THB categorized either by reading level easily understood, (2) practicality of the device can be seen from Keterlaksanaan RPP categorized very well, (3) Effectiveness learning tools can be seen from the thoroughness of individual student learning outcomes and the traditional, the effectiveness is also supported by the positive response of students to study indicated 95.83% of students who give a positive response. Based on data analysis can be concluded that the learning device by problem-oriented in curriculum 2013 on material factors that influence the reaction rate meets the criteria of quality, practicality, and effectiveness so that used in learning.